Tinjauan literatur terkemudian tentang wahdat al-adyan - Yusri Mohamad Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In spite of the very enigmatic nature of the figurative passages and wondrous stanzas of the Sufis, scholars from all over the world intrigued to get acquaintance with the meanings between the lines. Above all, one who indulges in inquiring “the unity of religions” would find rather perplexing, let alone “the unity of Being”. The Sufi conception of religious diversity is what its greatest adversary Ibn Taymiyyah considered as the apex of their heresies. Initial disclosure by scholars during the 19th century was filled with revelation and astonishment. Nevertheless, the highest ever tolerance portrayed by the Sufis later yet again denounced. But even so, traditional advocacy is far from being diminished with an addition of progressive inclination towards social reform, thus shaping new development of dynamic contour of the discourse.